1994
DOI: 10.1093/carcin/15.2.325
|View full text |Cite
|
Sign up to set email alerts
|

Dose-responses in rat hepatic protein modification and expression following exposure to the rat hepatocarcinogen methapyrilene

Abstract: Dose-related effects of methapyrilene (MP) on protein modification and expression were examined using two-dimensional gel electrophoresis (2-D PAGE) coupled with computer analysis. Methapyrilene was administered ad libitum at doses of 0, 62.5, 125, 250 and 1000 p.p.m. to male F-344 rats for 12 weeks beginning at 8 weeks of age. Following treatment, livers were removed and frozen for 2-D PAGE analysis. Separation of hepatic proteins was conducted using ISO-DALT technology. Changes in abundance and modification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…It has been suggested that it causes liver mitochondrial proliferation in the rat and has high binding affinity for mitochondrial proteins. 54 In our study, the carnitine profile remained the same and did not indicate changes in mitochondrial biogenesis or increased mitochondrial fatty acid β-oxidation. Increased relative concentrations of TAGs and decreased concentrations of PCs also suggest against any increase in β-oxidation and mitochondrial proliferation.…”
Section: Pharmacological Mode Of Action and Compound-specific Effectssupporting
confidence: 47%
See 1 more Smart Citation
“…It has been suggested that it causes liver mitochondrial proliferation in the rat and has high binding affinity for mitochondrial proteins. 54 In our study, the carnitine profile remained the same and did not indicate changes in mitochondrial biogenesis or increased mitochondrial fatty acid β-oxidation. Increased relative concentrations of TAGs and decreased concentrations of PCs also suggest against any increase in β-oxidation and mitochondrial proliferation.…”
Section: Pharmacological Mode Of Action and Compound-specific Effectssupporting
confidence: 47%
“…MP HCl causes liver toxicity and regenerative hyperplasia. It has been suggested that it causes liver mitochondrial proliferation in the rat and has high binding affinity for mitochondrial proteins 52 . In our study, the carnitine profile remained the same and did not indicate changes in mitochondrial biogenesis or increased mitochondrial fatty acid β- oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of rats with MP has been shown to form reactive metabolites that covalently bind specifically to mitochondrial proteins (50) and damage to the inner mitochondrial membrane has been proposed to play a significant role in MP toxicity (51,60). Co-incubation of MP-treated hepatocytes with phenylalkylamine Ca ++ channel blocker verapamil, but not treating the cells in a nominally Ca ++ -free medium, abrogated cell death and afforded approximately a 100-fold protection against MP effects suggesting that intracellular Ca ++ is involved in MP-induced cell death (44).…”
Section: Hamadeh Et Al Toxicologic Pathologymentioning
confidence: 99%
“…19 Two glucuronide conjugates of methapyrilene were also found in bile, however it is unclear how, if at all, they relate to the formation of a reactive metabolite. In rats methapyrilene induces liver mitochondrial proliferation 20 and promotes covalent modification of proteins within the organelle 21 which might be associated with the drug or a metabolite. 22 In isolated rat hepatocytes, inhibition of mitochondrial transition permeability pore opening and prevention of intracellular Ca 2+ mobilization reduced methapyrilene toxicity, strongly implicates loss of mitochondrial Ca 2+ homeostasis in the toxic mechanism.…”
Section: Introductionmentioning
confidence: 99%